Factors associated with the performance of episiotomy - Bruna Menezes Aguiar; Thales Philipe Rodrigues da Silva; Samire Lopes Pereira; Ana Maria Magalhães Sousa; Roberta Barbosa Guerra; Kleyde Ventura de Souza; Fernanda Penido Matozinhos (Revista Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze the factors associated with the performance of episiotomy. Methods: Cross-sectional study, developed with data from the research “Born in Belo Horizonte: Labor and birth survey, “conducted with 577 women who had their children via vaginal birth. In order to verify the magnitude of the association between episiotomy and its possible determinants, logistic regression models were constructed to estimate the odds ratio. Results: Episiotomy was performed in 26.34% of women, and 59.21% knew they had been subjected to it. We observed that younger women, primiparous women, women assisted by a professional other than the obstetric nurse and women who had their babies in a private hospital have an increased chance of being submitted to this procedure. Conclusion: Considering the rates of episiotomy, this study highlights the need for the absolute contraindication to indiscriminate performing it.